Influence of Emotion Regulation and Empathy on Thai Parenting Behavior: A Path Analytic Model - Nimkannon, Oratip; Weinstein, Ben (Scholar: Human Sciences, 2015)
Research has identified emotion regulation and empathy as the two factors that have strong associations with positive parenting behavior. It remains unclear, however, how emotion regulation, empathy, and parenting behavior are related. As an attempt to fill in this gap in research, the present study explored the influence of emotion regulation strategies, namely expressive suppression and cognitive reappraisal, and empathy on the parenting behavior of Thai parents who live in Bangkok, Thailand. The research design of this present study was cross-sectional and correlational, using the path analysis via multiple regression analysis to test the hypotheses. Two path models were tested, for fathers and mothers separately. Two hundred fifty-two parents were recruited from three schools, four private organizations, and a parenting network to voluntarily participate in this study. Results revealed that the relationships among the variables were significantly different for fathers and mothers. Specifically, cognitive reappraisal had no direct effect on positive/negative parenting behavior, while the effect of expressive suppression on negative parenting behavior was significant only for mothers. Similarly, the mediating effect of empathy on emotion regulation strategies and parenting behavior was significant only for mothers. Both models, however, showed that empathy was a significant predictor of parenting behavior, which was consistent with what previous studies found. Future studies should continue to explore the predictors of parental empathy, including the emotion regulation strategies that are relevant to the Thai parenting context.